Serum MiR-4687-3p Has Potential for Diagnosis and Carcinogenesis in Non-small Cell Lung Cancer - Liu, Man; Si, Qiufang; Ouyang, Songyun; Zhou, Zhigang; Wang, Meng; Zhao, Chunling; Yang, Ting; Wang, Yulin; Zhang, Xue; Xie, Wenbo; Dai, Liping; Li, Jitian (Frontiers in Genetics, 2020)
The lack of useful biomarker contributes to the increased mortality of non-small cell lung cancer (NSCLC) partly. MiRNAs have become increasingly appreciated in diagnosis of NSCLC. In the present study, we used microarray to screen 2549 miRNAs in serum samples from the training cohort (NSCLC, n=10; the healthy, n=10) to discover differentially expressed miRNAs (DEMs). Quantitative reverse-transcription polymerase chain reaction (qRT-PCR) assay was applied to validate the expression level of selected overexpressed DEMs of NSCLC in validation cohort (NSCLC, n=30; the healthy, n=30). Area under the receiver operating characteristic curve (AUC) was performed to evaluate diagnostic capability of the DEMs. The expression of the miRNAs in tissues was analyzed based on TCGA database. Subsequently, the target genes of the miR-4687-3p were predicted by TargetScan, Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis were tested by R software (ClusterProfiler package). NSCLC cells were transfected with inhibitor or mimic to down-regulate or up-regulate the miR-4687-3p level. The function of miR-4687-3p on proliferation, invasion, and migration of lung cancer cells were investigated through CCK-8 and Transwell assays, respectively. In the results, we identified serum miR-4687-3p that provided a high diagnostic accuracy of NSCLC (AUC=0.679, 95%CI: 0.543-0.815) in the validation cohort. According to TCGA database, we found that the miR-4687-3p level was significantly higher in NSCLC tissues than in normal lung tissues (p< 0.05). GO and KEGG pathway enrichment analysis showed that postsynaptic specialization and TGF-β signaling pathway were significantly enriched. Down-regulation of miR-4687-3p could suppress the proliferation, invasion, and migration of the NSCLC cells, compared with inhibitor negative control (NC). Meanwhile, overexpression of miR-4687-3p could promote the proliferation, invasion, and migration of the NSCLC cells compared with mimic NC. As a conclusion, our study first discovered that serum miR-4687-3p might have clinical potential as a non-invasive diagnostic biomarker for NSCLC and play an important role in the development of NSCLC.